THE APPLICATION OF STRICT LIABILITY PRINCIPLE IN ACEH PROVINCE'S FOREST FIRE CASES - Munira Rezkina; Sanusi Bintang (Student Journal of International Law, 2021)
This article investigates the reason that is likely to cause inaccurate interpretation by an Indonesian Court and the application of the 'strict liability' principle in Aceh forest fire cases. Mainly, this article discovers the cause of inaccurate interpretation of strict liability is an insufficient legal instrument and the lackness of law enforcement while applying the strict liability principle. It is proposed to amend the law and regulations that are inconsistent with one another to ensure the principle's application and outlines a comprehensive procedure for imposing strict liability on the plaintiff, defendant, and judge. Keywords: Strict liability principle; Strict liability; Forest fire; Aceh forest fire cases; Environmental law.